MATERIALS ADAPTATION OF IMPORTED CEFR TEXTBOOKS: TEACHERS’ PERCEPTIONS AND PRACTICES (Malaysian Journal of Learning and Instruction, 2024)
Purpose - This study aims to find out ESL teachers’ perceptions of imported CEFR textbooks currently in use in the classroom. Additionally, it seeks to determine how teachers have adapted and localized the contents of these books.Methodology - A total of 331 lower secondary school teachers participated in the survey and six were selected for face-to-face interviews. A questionnaire, utilizing a semantic differential scale ranging from one to six, was administered to collect quantitative data, while qualitative data was gathered through a semi–structured interview protocol.Findings - The results indicate that the majority of the teachers were fully aware of the CEFR imported textbooks currently being used in schools. Interestingly, more than half of the surveyed teachers (53.8%) agreed that these books were suitable and matched CEFR levels B1 and B2 set for the secondary school level.Significance - Findings from the interviews highlighted the necessity for teachers to adapt materials, although it also meant extra workload for them. As expected, the teachers added, modified, and simplified the contents of the textbooks. In short, materials adaptation is inevitable as long as the imported CEFR textbooks remain the main teaching materials.